The characterization in the head stack assembly (HSA) during the swaging process: optimization of actuator arm material - Kaewka, Weerapol; Tangchaichit, Kiatfa (Asia-Pacific Journal of Science and Technology, 2017)
This research studied the head stack assembly (HSA) swaging process, focusing on the head gimbal assembly(HGA)andtheactuatorarm. Thisprocessusesaball whichis swagedthroughabaseplate,acomponentof the HGA, toexpandandplasticallydeform thebaseplate,causingthebaseplatetoadjoin withtheactuatorarm. The actuator arm material was investigated to increase the efficiency of manufacturing process.Prediction of the stress behavior was analyzed by finite element method. This research used 5 types of aluminum with different strength suchas6063-T5,6063-T6,6061-T6,7005-T6and7005-T53. Amongthem, Aluminum 6061-T6is mostlyusedasan actuator arm. The result showed that the retention torque was increased when the actuator arm was stronger. However, the use of Aluminum 7005 T6 as actuator arm showed high torque value and least deformation of base plate. Therefore, Aluminum 7005-T6 was suitable for making the actuator arm.